To share or not? Factors influencing word of mouth communication - Goh, Chin Wei; Adam, Mohamad Zainol Abidin; Hoe, Chee Hee (2014)
In the consumer market, loyalty is an essential goal and a key element for a company to build a long-term sustainability and growth.Loyal consumers are more willing to make recommendations, advice and suggestions about a firms products to their friends or relatives through Word of Mouth (WOM) communication.In this relation, 90% of the advertising is viewed by consumers as non-credible while 90% of word of mouth communicated is treated as credible (Lee, Mullen and Fraedrich, 2011).The objective of this study is to determine the factors influencing word of mouth (WOM) communication among mobile phone users. Five factors which are Perceived Value, Perceived Quality, Customer Satisfaction, Brand Love and Brand Trust are examined to determine whether these factors influenced word of mouth communication.This study was conducted among 393 respondents from Universiti Utara Malaysia (UUM), Sintok Kedah.The methods used to analyse the data are Reliability test, Descriptive Analysis, ANOVA, Independent Sample T-Test, Pearson Correlation Analysis and Multiple Regression Analysis.The findings indicated that all these five factors have a strong positive relationship with Word of Mouth communication.The results also showed that Brand Love had the strongest significant positive relationship with Word of Mouth communication with correlation value of 0.802, followed by Brand Trust with correlation value of 0.793.In addition, Pearson correlation analysis results showed that Brand Trust and Brand Love are factors that strongly influenced Word of Mouth communication. This study provides an understanding of the factors that drives word of mouth communication by a consumer.Word of mouth can be a main potential source for business to grow and hence it is very important for marketers to understand it.